Cure of a CD20-positive peripheral T-cell lymphoma-NOS with CHOPE regimen plus surgery a case report and literature review - Chi, Chenyu; Wang, Shuo; Xu, Man; Shi, Yue; Ran, Xuehong (Frontiers in Medicine, 2025)
Peripheral T-cell lymphoma non-specific type (PTCL-NOS) is the most common subtype of mature T-cell tumors, which is clinically characterized by high invasiveness and poor prognosis. It is worth noting that PTCL-NOS rarely abnormally expresses B-cell antigens (such as CD20). This rare immunophenotype makes it easily confused with B-cell non-Hodgkin’s lymphoma (B-NHL), which brings challenges to clinical diagnosis and may lead to wrong treatment decisions. At present, CHOP regimen, as the first-line standard therapy for PTCL-NOS, has the limitations of low complete remission rate and high recurrence risk. In order to improve the efficacy, recent studies have confirmed that the combination of etoposide (CHOPE regimen) on the basis of CHOP regimen can significantly improve the treatment response for newly diagnosed patients aged ≤ 65 years. This paper reports a rare case of PTCL-NOS with abnormal expression of CD20 in the tongue. The patient received four cycles of CHOPE regimen after surgical resection of the primary tumor and underwent PET/CT mid-term evaluation. Through this case, we aim to further explore the pathological diagnosis difficulties of such rare cases and preliminarily evaluate the clinical application value of CHOPE regimen.